Clinical Selection of Prenatal Diagnostic Techniques Following Positive Noninvasive Prenatal Screening Results in Southwest China - Jing, Xiaosha; Liu, Hongqian; Zhu, Qian; Liu, Sha; Liu, Jianlong; Bai, Ting; Deng, Cechuan; Xia, Tianyu; Liu, Yunyun; Cheng, Jing; Wei, Xiang; Xing, Lingling; et al. (Frontiers in Genetics, 2022)
Background: This study aims to evaluate prenatal diagnosis methods following positive noninvasive prenatal screening (NIPS) results. Method: According to the positive noninvasive prenatal screening results, 926 pregnant women were divided into three groups: main target disease group (high risk for trisomy 21, trisomy 18, or trisomy 13), sex chromosome abnormality (SCA) group, and other chromosomal abnormalities group (abnormal Z-scores for chromosomes other than trisomy (T)21/T18/T13 or SCAs). The verification methods and results were then retrospectively analysed. Results: In the main target disease group, the positive rate of chromosomal abnormalities confirmed by quantitative fluorescence polymerase chain reaction (QF-PCR) was 75.18%(212/282), which was not significantly different from that by karyotyping (79.36%, 173/218 ) and copy number variation (CNV) detection methods (71.43%, 65/91). The positive rate of additional findings confirmed by karyotyping and CNV detection methods in main target disease group was 0.46%(1/218) and 8.79% (8/91), respectively. The positive rate of chromosomal abnormalities confirmed by karyotyping and CNV detection methods were 27.11% (45/166) and 38.46% (95/247) in the SCA group and 4.17% (1/24) and 20% (36/180) in the other chromosomal abnormalities group, respectively. Fetal sex chromosome mosaicism was detected in 16.13% (20/124) of the confirmed SCA cases. There were no significant differences in the detection rates of chromosomal microarray analysis (CMA) and CNV sequencing (CNVseq) among the three groups (P > 0.05). Conclusion: QF-PCR can quickly and accurately identify aneuploidies following NIPS-positive results for common aneuploidy, and in combination with karyotyping and CNV detection techniques can provide more comprehensive results. With the NIPS-positive results for SCA or other abnormalities, CMA and CNVseq may have the same effect on increasing the detection rate. The addition of fluorescence in situ hybridization (FISH) assay may help to identify true fetal mosaicism.